Does Indonesian millennial consider customer ethnocentrism and consumer’s aspiration on buying intentions? - Ainur Rofiq, Sumiati, Klemens W. Prasastyo, Surachman, (Opción, 2020)
This research investigates the effects of country of origin image (COO), consumer ethnocentrism (CE) and consumer’s aspiration (CA) on purchase intention (PI) by millennial in the emerging Indonesian Market. The research also investigates the moderating role of brand equity (BE) and quality perception (QP) on the relation between COO, CE, CA and PI. The sampling method used is non-probability sampling with purposive sampling technique. The empirical findings indicate that only consumer’s aspiration has a significant direct effect on purchase intention, whereas country of origin image and consumer ethnocentrism has no significant direct effect on purchase intention.